Memory, Art and Intergenerational Transmission: Artistic Practices with Young People in Memory Sites in Argentina - Tornay, Lizel (2024)
This text analyzes recent experiences with young people from Middle Schools in spaces of memory in the city of Buenos Aires, Argentina. These spaces of memory refer to the traumatic past related to the State terrorism imposed before and during the last military dictatorship (1975 and 1983). In particular, we examine the possibilities offered by artistic language for the elaboration of traumatic memories in order to facilitate the approach of new generations to this difficult past with which they coexist in one way or another.With this interest in mind, we analyse two experiences promoted by two spaces of memory that have proposed different strategies and initiatives. Both invite critical reflection on the recent past from sensitive experiences: the Poster Project of the Parque de la Memoria -Monumento a las Víctimas del Terrorismo de Estado and the reading of poetry written by a survivor during guided visits to the site of memory “El Olimpo”, former Clandestine Centre of Detention, Torture and Extermination.We argue that intergenerational transmission is not a unidirectional linear transfer of an unmodified object (knowledge and memories of the past) from adults to young people, but a dialogue where there is elaboration and translation by the new generations, according to their contexts, interests and questions of the present.